Pendampingan Penggunaan Teknologi Media dan Internet Bagi Pengurus Bumdes Teratai Indah Desa Nanti Agung Ilir Talo Kabupaten Seluma - Azizatul Banat; Mariska Febrianti; Martiani Martiani; Juwita Juwita; Gustini Gustini (Universitas Dehasen Bengkulu, 2022)
Technology is not limited to one particular field, or to a product, but can be in the form of materials and methods or techniques. While the word